Appropriate Surgical Repair of Ventricular Free Wall Rupture after Infarction: a Case Report - Umut Serhat Sanrı; Kadir Kaan Özsin; Faruk Toktaş; Şenol Yavuz (Brazilian Journal of Cardiovascular Surgery, 2019)
Abstract Ventricular free wall rupture is a fatal mechanical complication of acute myocardial infarction. In some cases it can be represented as subacute clinic and may not cause death in a few minutes. Acute pseudo-aneurysms are extremely unstable and bound to fatal rupture. Herein we report a male patient who suffered dyspnea and mild chest pain, 4 weeks after acute ST-segment elevation myocardial infarction.